Mekanisme Peningkatan Efisiensi Operasional melalui Digitalisasi Manajemen SHE: Peran Mediasi Kinerja Keselamatan di Proyek Batu Hijau - Wira Sanjaya Tapitapi; Tomy Dwi Cahyono (SENTRI: Jurnal Riset Ilmiah, 2026)
This study develops an integrated model explaining how digitalization of Safety, Health, and Environment (SHE) management can improve safety performance and operational efficiency in heavy-equipment service activities at the Batu Hijau Project. The model combines a socio-technical systems perspective, digital transformation capability, and the safety-performance framework. A quantitative explanatory case design was specified and evaluated with Partial Least Squares Structural Equation Modeling (PLS-SEM). Because project-level primary data were not supplied for this manuscript-development stage, the analytical model was tested using a calibrated simulated dataset of 132 observations representing frontline, supervisory, technical, and SHE-related roles. The measurement model met reliability and convergent-discriminant validity criteria. Digital SHE management showed a positive effect on safety performance (β = 0.718; p < 0.001) and operational efficiency (β = 0.415; p < 0.001), while safety performance positively affected operational efficiency (β = 0.459; p < 0.001). The indirect effect was also significant (β = 0.329; p < 0.001), indicating partial mediation. The findings suggest that integrated digital workflows, mobile reporting, real-time dashboards, traceable corrective actions, and data-driven learning can simultaneously strengthen preventive safety control and reduce administrative and coordination losses. The paper offers a practical digital-SHE architecture and measurable implementation priorities for mining-service operations.